Upaya Meningkatkan Hasil Belajar Keterampilan Gerak Passing Chest Pass Melalui Permainan Lempar Tangkap - Achmad Diky Muchafi; Muhammad Bambang Herinanta; Mochamad Ridwan (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This Classroom Action Research aims to describe the problems related to Physical Education learning, particularly the chest pass material. The effort to address this problem is through modified games using throwing and catching activities. The results of this study show an increase in learning outcomes for chest pass motor skills through throwing and catching games. After the treatment through throwing and catching games, the initial data showed that 86.21% or 25 students had not yet mastered the skill. However, after the first cycle of modification through throwing and catching games, there was an increase of 51.72% or 15 students who mastered the skill. In the second cycle, there was a further increase of 65.52% or 19 students who mastered the skill. Based on the research data, there was an improvement after the implementation of the improvement effort through throwing and catching games in grade XI-TKP (Technical Construction and Property) students at SMKN 3 Surabaya.